Young, Healthy, Underweight Women Require Higher Effective Doses of Propofol for Successful Gastroscope Insertion: a Dose-Finding Study Using Dixon’s Up-and-Down Method - Zhu Q; Cui L; Li X; Li Q; Wang Y (Drug Design, Development and Therapy)
Qian Zhu, Lingli Cui, Xinyue Li, Qipei Li, Yun Wang Department of Anesthesiology, Beijing Friendship Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Yun Wang, Department of Anesthesiology, Beijing Friendship Hospital, Capital Medical University, NO. 95 Yong-An Road, Xi-Cheng District, Beijing, 100050, People’s Republic of China, Tel +86-10-63138780, Email wangyun129@ccmu.edu.cnPurpose: The number of young women undergoing painless gastroscopy is rising annually. However, the lack of studies on the effective doses of propofol sedation for young, underweight women, presents a clinical challenge. Our study aimed to determine and compare the effective doses of propofol required for successful gastroscope insertion in normal-weight and underweight young women.Patients and Methods: Chinese women aged 18– 35 years who were of normal weight (18.5 ≤ body mass index (BMI) < 25 kg/m²) or underweight (BMI < 18.5 kg/m²) and were undergoing painless gastroscopy were included. The initial induction dose of propofol was 2.0 mg/kg, and subsequent doses were adjusted using the modified Dixon’s up-and-down method (step size: 0.1 mg/kg). The 50% and 95% effective dose of propofol (ED50 and ED95), defined as the doses required for successful gastroscope insertion in 50% and 95% of patients, respectively, were determined using the modified Dixon’s up-and-down method and isotonic regression analysis. All adverse events were documented.Results: Thirty patients were included in each group. The modified Dixon’s up-and-down method was used, and the ED50 of propofol was found to be significantly higher in patients in the underweight group (2.72 ± 0.23 mg/kg) than those in the normal-weight group (2.03 ± 0.13 mg/kg) (P < 0.001). The ED50 and ED95 in the normal-weight group extrapolated using isotonic regression analysis were 2.00 (83% confidence interval [CI], 1.900– 2.100) mg/kg and 2.30 (83% CI, 2.300– 2.400) mg/kg, respectively. In the underweight group, these values increased to 2.80 (83% CI, 2.700– 2.900) mg/kg and 3.00 (83% CI, 3.000– 3.100) mg/kg, respectively. The nonoverlapping CIs indicated significant differences between patients in the normal-weight and underweight groups.Conclusion: Young, healthy, underweight women require higher effective doses of propofol for deep sedation for successful gastroscope insertion compared with young, healthy, normal-weight women.Keywords: effective dose, propofol, gastroscope insertion, underweight women, normal-weight women